Continuous wave sub‐THz photonic generation with VCSEL‐based optical frequency comb. Issue 15 (1st July 2013) - Prior, E.; Criado, Á.R.; de Dios, C.; Acedo, P.; Ortsiefer, M.; Meissner, P.
Abstract : A simple and energy‐efficient photonic system to generate continuously tunable, low phase noise, sub‐THz waves based on COTS components is presented. The optical scheme is based on the use of a commercial vertical cavity surface emitting laser under gain switching modulation that provides a very flat optical frequency comb generator (OFCG) with 23 modes in a 20 dB bandwidth. The laser only needs 15 dBm continuous wave radiofrequency input power and 9 mA of bias current to provide this OFCG. Two optical injection locking stages filter and amplify the two desired modes that are detected in a photodiode to produce the desired sub‐THz signal at the frequency difference of these two selected modes. As an example, demonstrated is the generation of a very stable 88.2 GHz tone with lower linewidth than 10 Hz using a reference of 4.2 GHz to generate the OFCG.